Financial Management Practices of Coastal Fishermen Cooperatives in Supporting Blue Economy Growth - Adi, Roni; Wijaya, Erric; Rely, Gilbert; Samuel, Indah Elychia (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The growth of the blue economy in Indonesia is inseparable from the role of coastal communities, especially fishermen's cooperatives, which are the main forum in the management of fisheries businesses and the distribution of marine products. However, financial management practices in fishermen's cooperatives still face various challenges, such as low financial literacy of management, weak transparency of records, and limited access to formal capital institutions. This study aims to evaluate the financial management practices of coastal fisher cooperatives and examine their contribution in supporting blue economic growth. The research method uses a mixed approach, with the collection of quantitative data from the financial statements of fisher cooperatives and qualitative data through in-depth interviews with administrators and members. A total of 12 fishermen's cooperatives in the coastal areas of Central Java and South Sulawesi were selected purposively with the 2020–2023 observation period. The results of the study show that cooperatives that have a neater financial recording system, a savings and loan mechanism run well, and are able to access revolving funds from the government and Islamic financial institutions have succeeded in increasing working capital, expanding environmentally friendly fishing and aquaculture businesses, and contributing to marine resource conservation. In contrast, cooperatives with traditional financial management and dependence on member dues often experience limited liquidity, internal conflicts, and difficulty adapting to blue economy programs that demand efficiency and sustainability. These findings confirm that strengthening financial management practices through financial literacy education, the use of digital accounting technology, and regulatory support can strengthen the role of fishermen's cooperatives as key actors in supporting an inclusive and sustainable blue economy.